Sites of pluralism: community politics in the Middle East - Oruc, Firat (Oxford scholarship online Political Science, 2019)
Scholars and policymakers, struggling to make sense of the ongoing chaos in the Middle East, have focused on the possible causes of the escalation in both inter-state and intra-state conflict. But the Arab Spring has shown the urgent need for new ways to frame difference, both practically and theoretically. For some, a fundamental incompatibility between different ethno-linguistic and religious communities lies at the root of these conflicts; these divisions are thought to impede any form of political resolution or social cohesion. But little work has been done to explore how these tensions manifest themselves in the communities of the Middle East. 'Sites of Pluralism' fills this significant gap, going beyond a narrow focus on 'minorities' to examine the larger canvas of community politics in the Middle East.